THE IMAGE OF THE UZBEK BUSINESSWOMAN IN DOCUMENTARY FILMS OF THE 20TH–21ST CENTURIES - Muratova Elvira Raisovna (Sciental Journals Publishing, 2025)
The image of the modern Uzbek businesswoman in documentary films can be examined through several key aspects: her role in society, professional activity, the struggle against traditional stereotypes, and her contribution to cultural and economic transformations. This image often emerges in the context of significant changes in Uzbekistan, where women are increasingly asserting themselves in business, politics, and culture. Modern Uzbek businesswomen portrayed in documentaries often demonstrates high professionalism. They engage in entrepreneurial activities, manage large companies, or work on projects in fields traditionally considered "male."
Keywords: Businesswoman, documentary filmmaking, entrepreneurship, image, cinematography, trends, career growth, leadership qualities.